البيئة المصرفية السورية وأثرها في زيادة جودة المعلومات المحاسبية في ظل النظام المحاسبي المصرفي الموحد– دراسة ميدانية - حمزة, محي الدين; ملحم, مطيع (Latakia University Journal - Economic and Legal Sciences Series, 2013)
تتطلب التطورات التي حصلت في البيئة المصرفية السورية الحصول على المعلومات الجيدة والملائمة لضمان اتخاذ القرارات الأفضل, وخاصة في ظل التطورات المتسارعة والمنافسة المتزايدة من المصارف الخاصة التي تزايدت حصتها في السوق المصرفية السورية. تتناول هذه الدراسة العوامل المكونة للبيئة المصرفية السورية بما فيها العوامل القانونية والضوابط المهنية والعوامل التنظيمية والإدارية والعوامل التقنية والعوامل الثقافية والاجتماعية إضافة إلى العوامل الاقتصادية وأثر هذه العوامل البيئية في زيادة جودة المعلومات المحاسبية. ولتحقيق هدف الدراسة وزعت استبانة على العاملين في المصارف العامة السورية وتضمنت الاستبانة العوامل البيئية المكونة للبيئة المصرفية وخصائص جودة المعلومات المحاسبية وخلصت الدراسة إلى أن هناك تأثيرات ذات دلالة إحصائية لكل من العوامل المكونة للبيئة القانونية والضوابط المهنية والبيئة الاجتماعية والاقتصادية في حين لم يكن هناك تأثيرات للعوامل المكونة للبيئة التنظيمية والتقنية في زيادة جودة المعلومات المحاسبية. The developments that have occurred in the Syrian banking environment require getting good and appropriate information to ensure the best decisions, especially in the rapid developments and increased competition of private banks which have increased their share in the Syrian banking market. This study examines the constituent factors of Syrian banking environment including the legal, legislation, regulatory, administrative, technological, cultural, and social factors in addition to economic factors and the impact of these factors in the increasing of accounting information quality. To achieve the objective of the study a questionnaire distributed to employees in the Syrian public banks and the questionnaire included environmental factors constituting the banking environment and characteristics of the quality of the information. The study resulted that there are statistically significant effects for each of the constituting legal, social and economic environment factors, while there were no effects for constituent factors of the regulatory and technological environment in increasing the quality of accounting information.